Factors to Consider in the Use of Vital Signs Wearables to Minimize Contact With Stable COVID-19 Patients: Experience of Its Implementation During the Pandemic - Fan, Esther Monica Pei Jin; Ang, Shin Yuh; Phua, Ghee Chee; Chen Ee, Lee; Wong, Kok Cheong; Tan, Franklin Chee Ping; Tan, Lydia Wan Har; Ayre, Tracy Carol; Chua, Chee Yong; Tan, Benedict Wee Bor; Yeo, Khung Keong (Frontiers in Digital Health, 2021)
The COVID-19 pandemic has created a huge burden on the healthcare industry worldwide. Pressures to increase the isolation healthcare facility to cope with the growing number of patients led to an exploration of the use of wearables for vital signs monitoring among stable COVID-19 patients. Vital signs wearables were chosen for use in our facility with the purpose of reducing patient contact and preserving personal protective equipment. The process of deciding on the wearable solution as well as the implementation of the solution brought much insight to the team. This paper presents an overview of factors to consider in implementing a vital signs wearable solution. This includes considerations before deciding on whether or not to use a wearable device, followed by key criteria of the solution to assess. With the use of wearables rising in popularity, this serves as a guide for others who may want to implement it in their institutions.